Rare Presentation of Limb–Body Wall Complex in a Neonate: Case Report and Review of Literature - Omoloro Adeleke; Farrukh Gill; Ramesh Krishnan (American Journal of Perinatology Reports, 2022)
The limb–body wall complex (LBWC) aka body stalk syndrome is an uncommon congenital disorder characterized by severe malformations of limb, thorax, and abdomen, characterized by the presence of thoracoschisis, abdominoschisis, limb defects, and exencephaly. This condition is extremely rare with an incidence of 1 per 14,000 and 1 per 31,000 pregnancies in large epidemiologic studies. Majority of these malformed fetuses end up with spontaneous abortions. We present this rare case with occurrence in a preterm infant of 35 weeks' gestation. Our report highlights majority of the clinical presentations as reported in previous literature, but the significant pathological findings of absent genitalia and malformed genitourinary as well as anorectal malformations make this case presentation an even more rare occurrence. Infant karyotyping was normal male and there is no specific underlying genetic correlation in this condition which has a fatal prognosis.